Global urban development frameworks landing in Latin America: Insights from Ecuador and Bolivia - Blanc, Francesca; Cotella, Giancarlo (Development policy review, 2023)
Summary Motivation The global urban development frameworks defined by the United Nations are circulating worldwide and a race towards their domestic adoption has arisen since the approval of the New Urban Agenda and the 2030 Agenda for Sustainable Development. Their institutionalization at the domestic level is favoured by the rather aseptic “urban paradigm shift” that these documents present. However, the process according to which this happens is subject to path‐dependent logics and varies from one context to another. Purpose Stemming from the policy mobilities literature, the article explores the role that “pasteurized” urban narratives play in the domestic institutionalization of the global urban development frameworks. At the same time, it analyses how domestic institutional configurations have influenced their differential implementation in two Latin American countries. Methods and approach The article details the cases of the Ecuadorian National Urban Agenda and the Bolivian National Urban Policy, employing a mixed methodology that includes participant observation, consultancy activities, desk‐research, and semi‐structured interviews. Findings The analysis findings show that, on the one hand, the “comfortable landscape” offered by the “pasteurized concepts” that comprise the global urban development frameworks served as a “coalition magnet” favouring the building of consensus among stakeholders with rather different positions. On the other hand, however, this may result in a “fast‐track institutionalization” that prevents the concrete engagement of local governments in the process, in turn undermining the relevance of the results achieved. Policy implications Whereas further comparative research on the institutionalization of global urban development frameworks in Latin America and beyond is certainly needed, to further understand the hidden pitfalls of their domestic adoption, the evidence presented may contribute to inform the action of policy‐makers and practitioners dealing with their implementation at all levels.